387 The effects of ambient temperature on work-related injuries in adelaide, australia– workers' compensation claims increase with high temperatures. (24th April 2018) - Varghese, Blesson M; Barnett, Adrian G; Hansen, Alana L; Bi, Peng; Pisaniello, Dino L
Abstract : Introduction: Ambient thermal stress may directly, or indirectly, increase the risk of work-related injuries, particular for outdoor workers. However, little is known about the overall injury burden contributed by ambient temperatures (both high and low). The objectives of this study were to examine the relationship between ambient temperatures and work-related injuries and illnesses as well as quantify the associated burden at both ends of the temperature spectrum. Methods: Daily numbers of worker's compensation claims for injuries and illnesses in the Adelaide metropolitan area from 2003–2013 (n=224, 631) were provided by the jurisdictional regulator. Daily weather data were obtained from the Australian Bureau of Meteorology. We used a time-stratified case-crossover regression model combined with distributed lag non-linear to quantify the cumulative effect of temperatures over the previous 7 days. The burden of low and high temperatures was computed and further separated into effects related to mild and extreme temperature ranges. Analyses were stratified by worker, work environment and injury characteristics. Results: As the daily maximum temperatures rose above 25°C, the risk of work-related injuries and illnesses also increased. Compared with the optimum temperature (minimum claim likelihood), extreme high temperatures (99th percentile) were associated with a 30% (95% CI: 18% to 44%) increase in overall claims whereas no statistically significant association was observed with cold temperatures (1 st percentile). Longer delayed effects were seen for cold temperatures, whereas acute effects were seen in hot conditions. Notably, moderate temperature ranges were associated with greater injury burden than extreme temperatures. Conclusion: The results suggest a J-shaped relationship between temperature and injury claims with the highest extreme temperatures having the greatest risk but the more common hot days having the greatest burden. Companies and supervisors should be aware that heat-related injuries can arise even in moderately hot conditions. Injury prevention interventions should therefore consider ambient temperature risks more broadly.